Factors affecting the decision making process of African American students regarding the choice of hospitality management as a career - Bradford, Berkita S. (Kansas State University, 2005)
The purpose of this study was to identify factors affecting the decision process of African American students regarding the choice of hospitality management as a career. The significant influence of others, perception and awareness of the industry, resistance to servitude, and personal background were explored in the context of Omi and Winantâ s Racial Formation Theory. Focus groups were conducted with hospitality management and business students to investigate the above constructs in-depth. Questionnaires were administered to students enrolled in College of Businesses at 14 Historically Black Colleges and Universities who were majoring in hospitality management or some aspect of business. The results of the focus groups indicated that the students are aware that their race may determine what jobs they are offered in the hospitality industry, how rapidly they will be promoted, how society views them as individuals, and how society views an entire race when that particular race is found in low level jobs in large numbers or perception of an industry, and the pay scale. The students indicated that servitude is when one person has more power than someone else or someone is in control. Hospitality students were more likely to support the idea that the industry provides opportunities for advancements (Ï 2 = 33.64, df = 3, p < .001) and offer balanced pay in terms of race and ethnicity (Ï 2 = 14.49, df = 3, p < .01). For each servitude measure hospitality students were less likely to support notions of servitude in the hospitality industry than non-hospitality students. Non-hospitality students had a strong association with the idea that hospitality jobs are demeaning (Ï 2 = 10.16, df = 3, p < .05) and include positions that typically involved housekeeping and kitchen work (Ï 2 = 28.72, df = 3, p < .001). In general the data for African Americans revealed significant relationships between the outcome measure, career choice, and personal background (r = -.118, p < .05), awareness and perception of the hospitality industry (r = .116, p < .05) and significance of others (r = .164, p < .01) using two-tailed test.
Keywords: Career choice; Diversity; African Americans; Servitude; Hospitality management; Service; Sociology, Ethnic and Racial Studies (0631); Business Administration, Management (0454)